Rancang Bangun Aplikasi Pesan Tiket Online Swim Course Medan Berbasis Android - Ayyuna, Ifrah; Nadilla, Nur; Inayah, Anggita Dwi (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2025)
The development of information and communication technology has brought changes in various aspects of life, including purchasing tickets. Currently, many tourist and entertainment attractions provide online ticket purchasing services to make it easier for visitors. This can also be applied to swimming pools, where visitors can buy swimming tickets online via the application. The online swimming ticket application offers several benefits for visitors and swimming pool managers. Visitors can buy tickets easily and at any time, without having to queue at the ticket purchase counter. Apart from that, this application can also provide information about ticket availability, swimming pool opening hours and ongoing promotions. For swimming pool managers, this application can help increase ticket sales efficiency.